Relationship between Children's Playing Opportunities and Children's Gross Motor Development in Kindergarten Islam Kurnia Asy Syifa - Angry Fortuna Suryani Lubis; Vevi Sunarti (Universitas Negeri Padang, 2023)
The background of this research is the low gross motor development of children in Kurnia Asy Syifa Islamic Kindergarten, this is suspected because it has something to do with children's playing opportunities that are low. This study aims to: 1) describe children's play opportunities; 2) describe the development of gross motor skills of children; and 3) looking at the relationship between children's play opportunities and gross motoric development of children in the Islamic Kurnia Asy Syifa Kindergarten. This type of research is quantitative research with correlational descriptive techniques. The research population was all parents of students at Kurnia Asy Syifa Islamic Kindergarten, totaling 25 people and all populations were used as samples. The data collection technique is in the form of a questionnaire with a data collection tool in the form of a questionnaire. The data analysis technique uses the percentage formula and Spearman rho correlation. The results showed that: (1) children's playing opportunities were categorized as very low, (2) children's gross motor developmentwas categorized as very low, (3) there was a significant relationship between children's playing opportunities and children's gross motoric development in Kurnia Asy Syifa Islamic Kindergarten. It is suggested that parents can identify their children's motoric development and provide opportunities for children to develop their children's gross motor skills, one of which is through play activities. Keywords: gross motor, playing, PAUD